The Design of Enterprise Architecture Planning at PT. Glatia Plena Mas Motor Using the Zachman Framework - Muhammad Aldo; Devi Udariansyah (Institute of Information Technology and Social Science (IITSS), 2024)
This research aims to provide PT. Glatia Plena Mas Motor with a structured approach for achieving strategic advantages through the development of a formal business architecture. Using the Enterprise Architecture Planning (EAP) method, the study analyzes the company’s business processes and develops an architectural model based on the Zachman Framework. This framework is selected for its comprehensive ability to integrate business, information, application, and technology architectures. The resulting design includes a web-based application that centralizes key transactional information. Its implementation is expected to improve decision-making, streamline operational planning, and strengthen the company’s alignment with its strategic objectives.